2006
DOI: 10.1007/s10562-006-0079-x
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Characterization of Mesoporous Ti–Silica Hollow Spheres

Abstract: Titanium-silica hollow spheres (TSHS) with a mesoporous shell were synthesized using an inverse multiple oil-water-oil (O/W/ O) emulsion. These novel materials show interesting potential for catalysis. Excellent catalytic performance was found in the epoxidation of cyclohexene with tert-butylhydroperoxide. The investigation of the titanium environment by UV-vis, Raman and FTIR spectroscopy showed that at low Ti loading only isolated species are present and catalytic measurements demonstrated that these species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Evidence of such Ti-O-Ti oligomers was found during diffuse reflectance UV-Vis experiments, with the presence of a weak shoulder at 270 nm [82,83] ( Fig. 2-bottom left).…”
Section: Determining the Factors That Affect Catalytic Activitymentioning
confidence: 76%
“…Evidence of such Ti-O-Ti oligomers was found during diffuse reflectance UV-Vis experiments, with the presence of a weak shoulder at 270 nm [82,83] ( Fig. 2-bottom left).…”
Section: Determining the Factors That Affect Catalytic Activitymentioning
confidence: 76%
“…Due to the larger volume of Ti(O i Pr) 4 , this change was more obvious for sample c. In addition, the diffraction peak corresponding to the bulk TiO 2 (2h = 25.5) in the high degree region does not appear for both treated MCM-48 samples (not shown here) and their UV-visible spectra (see the supporting material, Fig. 1) also do not have the characteristic peaks of bulk TiO 2 [14]. Both of these suggested that the hydrolyzation of Ti-source happens rarely during the incorporation process.…”
Section: Resultsmentioning
confidence: 86%
“…The production of a stable solution of aqueous hollow silica spheres suggests applications of these materials in catalysis [25,60], coating technology, transport and controlled release of drug compounds [23]. Techniques to improve the stability of the silica hollow spheres were investigated for the system of CPB/SPFO templated silica spheres, which are less stable than the HFDPC/ SPFO system using the acid-catalyzed synthesis procedure described in Section 3.7.…”
Section: Stable Silica Hollow Spheres In Cpb/spfomentioning
confidence: 99%